Affirmative Action and Employment Equity: Policy, Ideology, and Backlash in Canadian Context - Bakan, Abigail B.; Audrey, Kobayashi (Studies in Political Economy, 2007)
Employment equity became a significant public policy issue in Canada following the 1984 publication of Equality in Employment: A Royal Commission Report² under the direction of Commissioner Rosalie Abella. Abella consulted widely with individual advocates and representatives of social movements to capture the growing concern for equality and equity issues that had crystallized with the adoption of the Charter of Rights and Freedoms. The result was a unique, Canadian approach to equity and it guided the development of a public policy agenda in very significant ways. However, the significance was not only in the establishment of a political culture friendly to an ideology of inclusiveness in the country’s workplaces; it also laid the ground for an acceptance of, and concessions to, certain aspects of political backlash. --Introduction